Significance of PTEN Mutation in Cellular Process, Prognosis, and Drug Selection in Clear Cell Renal Cell Carcinoma - Fan, Caibin; Zhao, Chunchun; Wang, Fei; Li, Shugen; Wang, Jianqing (Frontiers in Oncology, 2019)
It is well established that PTEN (Phosphatase and Tensin Homolog) mutant is a frequently mutated gene in clear cell renal cell carcinoma (ccRCC), making it a potential biomarker for individualized treatment opinions. Here, in the present study, we designed to evaluate the significance of PTEN mutations in prognosis and drug selection in ccRCC, and to find out potential changing pathways and genes associated with the mechanisms. Latest TCGA data showed PTEN mutations in 5% ccRCC patients. In total, 2569 genes were identified as DEGs. GO and KEGG analysis suggested that DEGs were significantly enriched in categories associated with cell division and multiple metabolic progression. The top ten genes ranked by degree were identified as hub genes from the protein–protein interaction network. What’s more, patients with PTEN mutation were associated with worsened prognosis of ccRCC. Data from GDSC database indicated that the selective AKT inhibitor GSK690693 as a selective inhibitor for ccRCC with PTEN mutation. Our findings have indicated that multiple genes and pathways may play a crucial role in PTEN mutation ccRCC, offering candidate targets and strategies for PTEN mutation ccRCC individualized treatment.